Pengaruh Pengaruh Profitabilitas, Leverage dan Ukuran Perusahaan Terhadap Tax Avoidance Pada Perusahaan Farmasi Yang Listing Di BEI Periode 2016-2022 - Pangestu, Ilham Tegu; Nasution, R (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to examine both partially and simultaneously the effect of Profitability, Leverage and Company Size on Tax Avoidance in pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2016 – 2022. The method used is a quantitative method, with data analysis using classical assumption test analysis, descriptive analysis, verification analysis, and hypothesis testing. The data source used is secondary data obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id) and the company's official website. The population in this study were pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2016 – 2022. The sampling technique used in this study was purposive sampling, so the samples used in this study were 6 pharmaceutical companies. Based on the results of the study, it was found that (1) Profitability partially has a significant effect on Tax Avoidance, (2) Leverage partially has a significant effect on Tax Avoidance, (3) Company size partially has no significant effect on Tax Avoidance. (4) Profitability, Leverage and Firm Size simultaneously have a significant effect on Tax Avoidance.